Are Individuals with Schizophrenia or Schizotypy More Creative? Evidence from Multiple Tests of Creative Potential. Issue 2 (3rd April 2017) - Wang, Lixia; Xu, Xiaobo; Wang, Qing; Healey, Grace; Su, Liang; Pang, Weiguo
Abstract : Schizophrenia and schizotypy have been often associated with above average creativity; however, empirical studies on the relationship between schizophrenia spectrum disorders and enhanced creativity generated inconsistent results. This research investigates if the association between schizophrenia spectrum disorders and creative potential levels is dependent upon which cognitive processes are examined during administered tests of creative potential. Our study examined 117 participants stratified into the following three subgroups: (a) 39 psychometrically determined low-schizotypal individuals, (b) 35 psychometrically determined high-schizotypal individuals, and (c) 43 patients with schizophrenia. Each participant completed 2 divergent thinking (DT) tasks, 2 convergent thinking (CT) tasks, and 2 creative tasks that combine both DT and CT processes. The data suggest that Group C had typical abilities in the DT, CT, and the combined creative thinking tasks; however, the group as a whole had intact originality during the Figural Completion (DT task) and the Tangram Construction (combined task). Notably, Group B showed significant advantages in both verbal and figural DT tasks. Group A and Group B demonstrated no significant differences in the creative thinking processes of CT; however, both groups outperformed Group C in these tasks.